2013
DOI: 10.4314/tjpr.v12i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Pattern of Vancomycin in a University Teaching Hospital in Oman: Comparison with International Guidelines

Abstract: Purpose: To assess the prescribing and utilization pattern of vancomycin in Sultan Qaboos UniversityHospital (SQUH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
(26 reference statements)
4
8
0
Order By: Relevance
“…[11] Many studies performed to evaluate vancomycin prescription according to the guidelines which listing appropriate and inappropriate situations for vancomycin use. [6121314151619]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[11] Many studies performed to evaluate vancomycin prescription according to the guidelines which listing appropriate and inappropriate situations for vancomycin use. [6121314151619]…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of several performed studies in the past decade showed, up to 88% appropriate use of vancomycin based on CDC recommendation. [6141516]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations